NATURE PLAY TO ENHANCE CHILDREN'S CREATIVITY: A CLASSROOM CASE STUDY OF "BRINGING PLANTS INTO THE CLASSROOM" - Xu, Yanfei; Abdul Rahman, Mohd Nazri (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates the implementation and effectiveness of the nature play activity “Bringing Plants into the Classroom” in enhancing the creativity of young children. Method: Conducted in a Chinese kindergarten setting with 24 children aged 4–5 and two teachers, the study utilized classroom observations, teacher interviews, and analysis of children's creative works. The activity involved plant classification, observation, and measurement to engage children in hands-on learning experiences. Results: Findings demonstrate that well-structured nature play activities significantly promote children's creativity, enhance observational and scientific exploration skills, foster emotional engagement, and support the development of teamwork and hands-on abilities. Novelty: This study provides empirical evidence on the educational value of nature play within the early childhood curriculum in a Chinese context, highlighting its potential to support holistic cognitive and emotional development through experiential learning. The research offers a practical model for integrating nature-based pedagogies into structured classroom environments to cultivate young learners’ creative and scientific competencies.